Tính
60+12+[-17]+[-43]
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) (-12) + 25 + 75 + 12 = (-12) + 12 + 25 + 75 = 0 +100 = 100.
b) 60 +12 + (-17) + (-43) = 60 + [(-47) + (-43)] +12.
c) (-2) + (-87) + (-18) + 87 = [(-2) + (-18)] + [(-87) + 87].
d) (-1)+(-2) + 36 + (-17) = 36+[(-1) + (-2) + (-17)].
a,24.57+43.24
=24.(57+43)
=24.100
=2400
b,12.19+12
=12.(19+1)
=12.20
=12.10.2
=120.2
=240
c,43.27+93.43+57.61+59.57
=43.(27+93)+57.(61+59)
=43.120+57.120
=120.(43+57)
=120.100
=12000
d,64.6+81.4+17.6
=64.6+27.3.2.2+17.6
=64.6+54.6+17.6
=(64+54+17).6
=135.6
=810
a) 24 . 57 + 43 . 24
= 24 . (57 + 43)
= 24 . 100
= 2400
b) 12 . 19 + 12
= 12 . (19 + 1)
= 12 . 20
=240
c) 43 . 27 + 93 . 43 + 57 . 61 +59 . 57
= 43 . ( 27 + 93) + 57 . (61 + 59)
= 43 . 120 + 57 . 120
= 120 . (43 + 57)
= 120 . 100
= 12000
Bài 1:
a: =25+75=100
b: =60-17-43+12=12
c: =-2-18=-20
d: =-3+36-17=36-20=16
Bài 2:
a: =-102
b: =-1000
c: =12x15=180
d: =21x(-10)=-210
15x27 > 4812 : 12 vì 405 > 401
13545 : 43 < 33 x 17 vì 315 < 561
7 + ( -12 + 43 ) - [ 7 + ( 43 - 17 ) ]
= 7 + ( -12 ) + 43 - [ 7 + 43 - 17 ]
= 7 + ( -12 ) + 43 - 7 - 43 +17
= ( 7 - 7 ) + ( 43 - 43 ) + [ ( -12 ) + 17 ]
= 0 + 0 + 5
= 5
12 giờ 43 phút + 17 giờ 17 phút = 30 giờ
50 phút 30 giây - 40 phút 15 giây = 10 phút 15 giây
12
12